A force-balanced control volume finite element method for multi-phase porous media flow modelling - Gomes,JLMA; Pavlidis,D; Salinas,P; Xie,Z; Percival,JR; Melnikova,Y; Pain,CC; Jackson,MD (International Journal for Numerical Methods in Fluids, 2016)
A novel method for simulating multi-phase flow in porous media is presented. The approach is based on acontrol volume finite element mixed formulation and new force-balanced finite element pairs. The novelty ofthe method lies in: (a) permitting both continuous and discontinuous description of pressure and saturationbetween elements; (b) the use of arbitrarily high-order polynomial representation for pressure and velocityand (c) the use of high-order flux-limited methods in space and to time avoid introducing non-physicaloscillations while achieving high-order accuracy where and when possible. The model is initially validatedfor two-phase flow. Results are in good agreement with analytically obtained solutions and experimentalresults. The potential of this method is demonstrated by simulating flow in a realistic geometry composed ofhighly permeable meandering channels.